Aligning physical learning spaces with the curriculum: AMEE Guide No. 107. (2nd August 2016) - Nordquist, Jonas; Sundberg, Kristina; Laing, Andrew
Abstract: This Guide explores emerging issues on the alignment of learning spaces with the changing curriculum in medical education. As technology and new teaching methods have altered the nature of learning in medical education, it is necessary to re-think how physical learning spaces are aligned with the curriculum. The better alignment of learning spaces with the curriculum depends on more directly engaged leadership from faculty and the community of medical education for briefing the requirements for the design of all kinds of learning spaces. However, there is a lack of precedent and well-established processes as to how new kinds of learning spaces should be programmed. Such programmes are essential aspects of optimizing the intended experience of the curriculum. Faculty and the learning community need better tools and instruments to support their leadership role in briefing and programming. A Guide to critical concepts for exploring the alignment of curriculum and learning spaces is provided. The idea of a networked learning landscape is introduced as a way of assessing and evaluating the alignment of physical spaces to the emerging curriculum. The concept is used to explore how technology has widened the range of spaces and places in which learning happens as well as enabling new styles of learning. The networked learning landscaped is explored through four different scales within which learning is accommodated: the classroom, the building, the campus, and the city. High-level guidance on the process of briefing for the networked learning landscape is provided, to take into account the wider scale of learning spaces and the impact of technology. Key to a successful measurement process is argued to be the involvement of relevant academic stakeholders who can identify the strategic direction and purpose for the design of the learning environments in relation to the emerging demands of the curriculum.